Metastatic Brain Tumors - Ersin Haciyakupoglu; Kadir Oktay; Semih Kivanc Olguner; Dervis Mansuri Yilmaz; Sebahattin Haciyakupoglu (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Metastatic tumor is secondary spread to the central nervous system of primer systemic cancers originating from tissues other than the central nervous system. In adults; there are metastases respectively from lungs, breasts, malign melanoma, renal cell carcinoma, colon and thyroid cancers. 30-60% of lung cancers metastasis to the brain. In children there are quite a few cerebral metastases. Most commonly leukemia, lymphoma, osteogenic sarcoma, rhabdomyosarcoma and germ cell tumors metastasis to the brain. %50 of malign melanoma, lung, breast and colon cancers intend to make multipl metastases but renal cell cancers intend to make solitary metastasis.While lung cancers metastasis to brain in 6-9 months after the definitive diagnosis, renal cancers in 1 year, colon cancers in 2 years, breast cancers and malign melanoma in 3 years metastasis to brain. In 6% of cases there are cerebral metastasis while there isn’t a symptom of a primary tumor. For treatment corticosteroids, surgery, Radiotherapy(RT), Chemotherapy(CT) and Stereotactic Radiosurgery(SRS) can be implemented. Small cell lung cancers, lymphoma, germ cell tumors are sensitive to RT and CT. Non small cell lung cancers, renal, colon cancers and malign melanoma are radioresistant. The purposes in the surgery of the metastatic brain tumors are; total resection of tumors without neurologic deficits, decreasing the intracranial pressure and decreasing the dose of postoperative radiotherapy.